Current situation and prospects of coalbed methane exploration and development in Sichuan Basin - ZHU Suyang, LIU Wei, WANG Yunfeng, JIA Chunsheng, CHEN Chaogang, PENG Xiaolong (Youqicang pingjia yu kaifa)
The Sichuan Basin is abundant in coal resources and has achieved breakthroughs in coalbed methane exploration wells in recent years. To explore the feasibility of establishing a coalbed methane production base in the Sichuan Basin, this study reviews the stratigraphic development of coalbed methane reservoirs in the Sichuan Basin, as well as the geological and dynamic characteristics of coalbed methane development blocks in the southeastern and southern regions of Sichuan. The first coalbed methane production base in the Sichuan Basin, the Junlian-Mu’ai mining area, has more than 450 surface extraction wells, with an annual gas production of over 1.00×108 m3 for five consecutive years. In the Shunan mining area, there are 328 production wells, with an annual gas production of 0.79×108 m3. However, in the basin, the average daily production of coalbed methane wells targeting coal seams is less than 700 m3, while pilot exploration wells that apply general fracturing to coal seams and adjacent sandstone layers can achieve production rates of 5 000 to 8 000 m3/day. This indicates that the production dynamics of coalbed methane in the Sichuan Basin differ significantly from those in other domestic coalbed methane production bases. This difference is attributed to the widespread development of thin coal seams and the structural coal layers interbedded with tight sandstone. Consequently, it is not appropriate to apply the “sweet spot” evaluation and development methods used for typical thick coal seams in basins such as the Qinshui Basin and Ordos Basin. There is an urgent need to shift away from the approach of considering only coal seams as the sole target layer for coalbed methane wells. Practice shows that coal seams in the Sichuan Basin are primarily developed in transitional marine-continental strata. Although the lateral development of coal seams is not stable, a stable combination of “coal, sandstone, and mudstone” has formed. This special lithologic combination can create “coal-sand-coal” hydrocarbon source storage boxes, which is of significant importance for the development and production capacity of thin interbedded coal seams in the Sichuan Basin. Moreover, a large number of coal mines in the Sichuan Basin have been shut down in recent years, and the coalbed methane accumulated in the abandoned mines urgently requires secondary development using surface drilling techniques. In conclusion, based on the geological resources and existing extraction technologies in the Sichuan Basin, it is feasible to establish the third coalbed methane industry base, following the Qinshui Basin and the eastern edge of the Ordos Basin.